Cost effectiveness of self monitoring of blood glucose in patients with non-insulin treated type 2 diabetes: economic evaluation of data from the DiGEM trial. Issue 7654 (17th April 2008) - Simon, Judit; Gray, Alastair; Clarke, Philip; Wade, Alisha; Neil, Andrew; Farmer, Andrew
Abstract : Objective To assess the cost effectiveness of self monitoring of blood glucose alone or with additional training in incorporating the results into self care, in addition to standardised usual care for patients with non-insulin treated type 2 diabetes. Design Incremental cost utility analysis from a healthcare perspective. Data on resource use from the randomised controlled diabetes glycaemic education and monitoring (DiGEM) trial covered 12 months before baseline and 12 months of trial follow-up. Quality of life was measured at baseline and 12 months using the EuroQol EQ-5D questionnaire. Setting Primary care in the United Kingdom. Participants 453 patients with non-insulin treated type 2 diabetes. Interventions Standardised usual care (control) compared with additional self monitoring of blood glucose alone (less intensive self monitoring) or with training in self interpretation of the results (more intensive self monitoring). Main outcome measures Quality adjusted life years and healthcare costs (sterling in 2005-6 prices). Results The average costs of intervention were £89 (€113; 179) for standardised usual care, £181 for less intensive self monitoring, and £173 for more intensive self monitoring, showing an additional cost per patient of £92 (95% confidence interval £80 to £103) in the less intensive group and £84 (£73 to £96) in the more intensive group. No other significant cost difference was detected between the groups. An initial negative impact of self monitoring on quality of life occurred, averaging −0.027 (95% confidence interval−0.069 to 0.015) for the less intensive self monitoring group and −0.075 (−0.119 to −0.031) for the more intensive group. Conclusions Self monitoring of blood glucose with or without additional training in incorporating the results into self care was associated with higher costs and lower quality of life in patients with non-insulin treated type 2 diabetes. In light of this, and no clinically significant differences in other outcomes, self monitoring of blood glucose is unlikely to be cost effective in addition to standardised usual care. Trial registration Current Controlled Trials ISRCTN47464659 .